Proteomics of snake venoms from Elapidae and Viperidae families by multidimensional chromatographic methods - Nawarak J. (2014)
Snake venoms contain a large number of biologically active substances and the venom components are very useful for pharmaceutical applications. Our goal is to separate and identify components of snake venoms in ten snake species from the Elapidae and Viperidae families using multidimensional chromatographic methods. The multidimensional chromatographic methods include reversed-phase high-performance liquid chromatography (RP-HPLC), sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), lab-on-a-chip, two-dimensional electrophoresis (2-DE), and mass spectrometry. The venoms of eight snake species demonstrated major differences in hydrophobicity, molecular weight separations, and 2-DE protein distribution patterns. The 2-DE images showed major differences between families, within each family and even between the same species. Venoms of the Elapidae family showed many basic proteins with a wide range of molecular weights, while venoms of the Viperidae family showed wide ranges of p/ and molecular weights, especially for Trimeresurus sp. The multidimensional chromatographic methods revealed specific differences in venom proteins intra-species as well as between species and families. We have isolated and identified proteins that may be unique for each species for further studies in the proteome of snake venoms and their potentially use in the pharmaceutical applications.